(untitled) (Italian Review of Legal History, 2022)
The classic definition of sovereignty, as a monopoly of legitimate violence within a territory delimited by borders, is intimately linked to the structure and history of the modern state, to the point that the crisis of the state, due to the processes of globalization, concerns the role of sovereignty on the international scene. Political anthropology, from Evans-Pritchard, seems unable to elaborate a paradigm of sovereignty capable of adapting to the transformations of other cultures after decolonization and the strong westernization of political structures. While sovereignty within the state makes the political leader the summa potestas and the holder of decision-making powers over the territory, Pierre Clastres has highlighted that some chiefs in other cultures are politically powerless, unable to exercise governmental powers and to impose their will. David Graeber’s anthropological perspective tries to bridge the gap between state sovereignty and kingship present in other cultures, arguing that sovereignty is a transcultural political structure, originally pertaining to the religious sphere. Starting from the analysis of the Shilluk, made famous by the studies of Sir James Frazer, Graeber searches for the characteristics of sovereignty common in all societies and identifies them in the transcendence of the sovereign with respect to the social fabric and in the intimate connection with violence. State sovereignty is not extraneous to these characteristics, and, on the contrary, the state order itself is seen as the development of the deepest aspirations of sovereignty: in fact, the States attempt the realization of a utopian project of social peace implemented through the use of of the violence of its apparatuses. The space of legitimation for the exercise of the sovereign’s powers is defined with the clash between the people, intent on limiting the exercise of sovereign powers within the ritual and within a limited geographical space, and the sovereign, aiming to extend his own powers. According to Graeber, this process would result in “the sacralization of the king”, that is, the attempt to contain the royal power within the religious sphere. The affirmation of modern sovereignty over the feudal regime can be seen as the product of a failed sacralization, in which the king triumphed. Sovereignty represents for Graeber a political archetype present in every human community. This means that it remains in its fundamental core, even where society undergoes significant changes. Although, in fact, sovereignty has mainly manifested itself in the form of the monarchy, it retains its characteristics even when several individuals share the role of political leadership. Kings never die, writes Graeber, their ghosts continue to inhabit the political community. Today the most widespread form of sovereignty is popular sovereignty, which represents the foundation and legitimacy of democratic regimes; however, for Graeber, popular sovereignty is incompatible with the state order and is paradoxical in itself. The state is incompatible with popular sovereignty firstly because it tends to the preservation of the established order, where the popular will could be fully manifested in the form of constant exercise of constituent power, and because it forces obedience through a coercive apparatus. In light of this, popular sovereignty is a paradoxical concept both from the logical point of view, since the sovereign, according to Graeber, cannot force himself into obedience, and from the historical point of view. Emblematic cases in this latter sense are the United States Constitution, which was born as deeply undemocratic, and the repression of the Occupy Wall Street movement, whose adherents demanded and stressed the need for a radical change in the political and economic system. The reference to popular sovereignty, as happened with the appeal to democracy, is the result of political rhetoric, conditioned by the advent of mass society, but which is still in the hands of deeply undemocratic oligarchies. Graeber hypothesizes that the genesis of the concept of popular sovereignty originates in empires. In fact, within empires unity is not constituted so much on the basis of the reference to a single political leader, but from the fact that the different populations converge to the within a single army, that of the imperial nation. It is from these military formations that the idea of a nation and then of a sovereign people would come to life. While democracy appears unattainable within states, its origins and its best versions occurred within the frontier communities of the colonies subject to strong migratory flows and on pirate ships: these communities, in fact, brought together people from very different cultures, ethnic groups and traditions, which found themselves having to find inclusive decision-making methods capable of ignoring the reference to the political institutions of origin. The pirate ship becomes the paradigm of democratic space, a place where authentic democratic sovereignty is expressed, in opposition to the state structure. Graeber’s contribution, although not conclusive, is a perspective on sovereignty worthy of interest, since, on the one hand, it manages to mend the separation that the question of sovereignty opens between Western societies and other cultures, and, on the other hand, side, it subverts the narrative of Western exclusivism on democracy and popular sovereignty.